Structure of elbow joint revision arthroplasty - Alimurad G. Aliev (Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics, 2021)
Abstract. Introduction Current operations of elbow arthroplasty are accompanied by an extremely high rate of complications in the early and long-term periods. Therefore, along with the widespread growth of primary arthroplasty, there is a growing need for revision interventions. Purpose To study the age groups of patients at the time of primary and revision arthroplasty, to investigate the reasons of the first and repeated revisions, the scope of interventions, as well as the time since the previous AP. Materials and methods A retrospective analysis of 133 cases of elbow revision arthroplasty (111 patients) treated from 2003 to 2019 was conducted. The rate of re-revisions was 16.5 %. The study investigated the age of patients, reasons for the first and repeated revisions, the scope of interventions, as well as the time passed since the previous elbow arthroplasty. Results In the structure of primary and revision arthroplasty, there was a significant dominance of patients aged 51 to 60 years (25.4 % and 33.3 %, respectively). However, the total rate of patients under 40 years old in the group of primary arthroplasty was 33.5 %, and in the revision group it was 34.2 %. The most frequent reason in the first and repeated revisions was aseptic loosening: 47 % and 50 %, respectively, followed by PJI (23 % in both groups), dislocation (10 % and 18 %, respectively) and breaks of the implant's components (8 % and 4 %). Other complications were less common (12 % and 5 %, respectively). Most of the revisions for PJI were performed in the first year since the previous arthroplasty (56.7 %). In terms of aseptic instability, early and late periods were identified. The ratio of early revisions to the total number of primary arthroplasty during the entire time of the surgical team's work decreased from 19.4 % to 3.5 %. Discussion The observed number of young people in the age structure of primary and revision AP in the long term is likely to lead to an increase in the number of patients with severe bone defects. The data of our study demonstrate a significant decrease in the number of revisions over the past 5 years performed for early loosening, despite the general increase in the number of primary APs. Conclusion The study identified a considerable number of young patients, which could potentially lead to an increase in the number of repeated revisions and related problems, including pronounced bone defects and recurrent infection. All this actualizes the need to improve the technique of revision arthroplasty.